Generic building modeling for non-residential buildings (especially office buildings) - Weiß, Dirk; Tribulowski, Katja; Hirth, Stephan; Grunewald, John (E3S web of conferences, 2024)
To promote sustainability in construction, planning must include dynamic analysis of renewable energies, as traditional methods fall short for this transition. Building simulation, essential for future planning, is often hindered by the time and cost required for detailed modeling. The proposed solution, generic modeling, automates the creation of 3D building models using basic early data or regulations, reducing time and expense. This paper focuses on applying this method to office buildings, exploring its algorithm, methodology, and practical uses, while acknowledging its limitations in model variability. This automated approach facilitates early energy sustainability evaluation and has the potential to scale up to district-level modeling.